Cytokine profiles show heterogeneity of interferon-β response in multiple sclerosis patients. Issue 2 (April 2016) - Hegen, Harald; Adrianto, Indra; Lessard, Christopher J.; Millonig, Alban; Bertolotto, Antonio; Comabella, Manuel; Giovannoni, Gavin; Guger, Michael; Hoelzl, Martina; Khalil, Michael; Fazekas, Franz; Killestein, Joep; et al.
Abstract : Objective: To evaluate serum cytokine profiles for their utility to determine the heterogeneous responses to interferon (IFN)–β treatment in patients with multiple sclerosis (MS). Methods: Patients with relapsing-remitting MS (RRMS) or clinically isolated syndrome receiving de novo IFN-β treatment were included in this prospective, observational study. Number of relapses and changes in disability were assessed 2 years prior to and 2 years after initiation of treatment. Sera were collected at baseline and after 3 months on therapy. Cytokine levels in sera were assessed by Luminex multiplex assays. Baseline cytokine profiles were grouped by hierarchical clustering analysis. Demographic features, changes in cytokines, and clinical outcome were then assessed in the clustered patient groups. Results: A total of 157 patients were included in the study and clustered into 6 distinct subsets by baseline cytokine profiles. These subsets differed significantly in their clinical and biological response to IFN-β therapy. Two subsets were associated with patients who responded poorly to therapy. Two other subsets, associated with a good response to therapy, showed a significant reduction in relapse rates and no worsening of disability. Each subset also had differential changes in cytokine levels after 3 months of IFN-β treatment. Conclusions: There is heterogeneity in the immunologic pathways of the RRMS population, which correlates with IFN-β response.